Peruvian Party Politics: Still some Signs of Life? - Crabtree, John (Universidad del Pacífico, 2006)
More than most Latin American countries in recent times, Peru has seen party voting strength, organisation and loyalties eroded. Since the Fujimori period, however – when parties found themselves under systematic attack – the return to more normal electoral activity has opened up a space for parties to reemerge. The 2003 Law on Political Parties was designed to strengthen a pluralistic party system. However, the results proved disappointing. Three rounds of elections in 2006 did little to restore voter confidence in Peru's major parties; these remain 'top-down' affairs with only shallow roots in society. However, the November 2006 local elections suggested that new forces may be emerging at the meso- level of politics in tandem with social movements. Study of Peruvian politics requires its own decentralisation.